2015
DOI: 10.1089/scd.2014.0314
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Tenomodulin Results in Reduced Self-Renewal and Augmented Senescence of Tendon Stem/Progenitor Cells

Abstract: Tenomodulin (Tnmd) is a well-known gene marker for the tendon and ligament lineage, but its exact functions in these tissues still remain elusive. In this study, we investigated Tnmd loss of function in mouse tendon stem/progenitor cells (mTSPC) by implicating a previously established Tnmd knockout (KO) mouse model. mTSPC were isolated from control and Tnmd KO tail tendons and their stemness features, such as gene marker profile, multipotential, and self-renewal, were compared. Immunofluorescence and reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 37 publications
7
92
0
Order By: Relevance
“…TNMD is considered as a late tendon marker in chick and mouse embryos, and is expressed during the differentiation and muscledependent phase of limb tendon development (reviewed by Dex et al, 2016). Tnmd mutant mice display an altered structure of collagen fibrils, and reduced self-renewal and increased senescence of tendon progenitors, in post-natal tendons (Docheva et al, 2005;Alberton et al, 2015). TNMD was expressed in SCX-positive tendons in E9 chick limbs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TNMD is considered as a late tendon marker in chick and mouse embryos, and is expressed during the differentiation and muscledependent phase of limb tendon development (reviewed by Dex et al, 2016). Tnmd mutant mice display an altered structure of collagen fibrils, and reduced self-renewal and increased senescence of tendon progenitors, in post-natal tendons (Docheva et al, 2005;Alberton et al, 2015). TNMD was expressed in SCX-positive tendons in E9 chick limbs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Their role, increasing water content in these regions, provides resistance to compression 27 . The glycoproteins found in tendon include molecules such as lubricin 28 , tenascin-C, collagen oligomeric matrix component 29 (COMP) and tenomodulin 30 . Elastic fibres, composed of elastin, fibrillins 1 and 2, as well as other elastic fibre-associated molecules are also present 31; 32 .…”
Section: Tendon Compositionmentioning
confidence: 99%
“…Lastly, a Tnmd knockout mouse model study revealed that loss of Tnmd results in reduced proliferation and earlier onset of senescence in TSPCs (Alberton et al 2015). The study compared tenogenic markers in both genotypes of which no differences were observed, except for the absence of Tnmd transcript in mutant mice.…”
Section: Tenomodulinmentioning
confidence: 99%